Movement Disorder Following Hypoglycemic Encephalopathy in Mitochondrial 3-Hydroxy-3-methylglutaryl-CoA Synthase-2 (mHS) Deficiency - Mayowa A. Osundiji; Alicia Chen; Joseph D. Farris; Radhika Dhamija (Annals of Internal Medicine: Clinical Cases)
Mitochondrial 3-hydroxy-3-methylglutaryl-coenzyme A synthase (mHS) deficiency is an ultra-rare inborn error of ketone body synthesis that is caused by biallelic mutations in HMGCS2. The manifestations of mHS deficiency can include hypoketotic hypoglycemia, metabolic acidosis, lethargy, encephalopathy, hyperammonemia, and hepatomegaly. Here, we report a case of movement disorder following hypoglycemic encephalopathy involving the basal ganglia in a patient with mHS deficiency. Exome sequencing showed novel compound heterozygous variants in HMGCS2, a partial gene deletion (classified as pathogenic) and c.704T>A (p.M235K) variant that was deemed to be likely pathogenic. Our findings suggest that mHS deficiency can result in basal ganglia injury and movement disorder.